Preventing Stunting in Dryland Areas with Cultural Communication Strategies - Marni Marni; Ribka Limbu; Sintha Lisa Parimahua (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Malnutrition, especially child stunting in Indonesia, including Kupang Regency, NTT Province, is a serious problem. Stunting affects 149.2 million children under 5 years old worldwide. In Kupang District in 2023, the prevalence of stunting is 13.0%. Factors such as climatic conditions, food insufficiency, and culture contribute to this problem. Stunting stunts child growth, reduces intelligence, and affects the economy. Prevention efforts involve national strategies including behavior change communication campaigns, including the important role of posyandu cadres. Posyandu cadres have credibility with receptive audiences. Communication skills with status, power of persuasion, and the ability to sensitize on the virtues of individual health and nutrition with personal proximity (Anshel and Smith, 2013). Posyandu cadres can be effective agents promoting behavior change. The delivery of health messages is one of the factors that can influence behavior change. As a culturally embedded society, cultural communication is the most frequently used language and communication that is most easily absorbed as a source of community information. Methods: The type of research used is Sequential Exploratory Mixed Methods. A combination research method where two phases of research, namely the first phase using qualitative methods and the next phase using quantitative methods, are based on the results of phase one. The combination of data from both methods is connecting the results of the first phase of research (qualitative research results) and the next phase (quantitative research results). The study was conducted in Semau sub-district for six months involving 30 mothers in the intervention group and 30 mothers in the control group. intervention group and 30 mothers in the control group. The East Nusa Tenggara Provincial Government and the Kupang Regency Government have granted permission and recommendations for this study, which also proposes ethical considerations from the Research Ethics Commission of the Faculty of Public Health, Nusa Cendana University, with ethical approval recommendation letter number No. 2024143 – KEPK. Results: The results showed a difference in the pre-test and post-test results in the intervention group and control group. The intervention group with a cultural communication approach showed a greater change than the control group. The post test results showed that knowledge in the intervention group increased dramatically to (63.6%) while the control group also experienced changes in knowledge (21.2%). Changes in perception in the intervention group also increased (72.7%) while perception in the control group (75.8%). Attitude changes in the intervention group (81.8%) and attitude changes in the control group (78.8%). As well as changes in the practice of the intervention group (90.9%) and in the control group (57.6%). Conclusion: Health promotion with a cultural communication strategy in Semau Sub-district shows maximum changes in knowledge, perceptions, attitudes and practices because people are more accustomed to local communication styles so that they are easier to understand, trust and apply. Based on these results, future researchers can examine other variables such as the effect of family support with cultural communication on accelerating stunting reduction in dryland areas.